Coupled Aqua and Ridge Planets in the Community Earth System Model. (23rd April 2021) - Wu, Xiaoning; Reed, Kevin A.; Wolfe, Christopher L. P.; Marques, Gustavo M.; Bachman, Scott D.; Bryan, Frank O.
Abstract: Idealized models can reveal insights into Earth's climate system by reducing its complexities. However, their potential is undermined by the scarcity of fully coupled idealized models with components comparable to contemporary, comprehensive Earth System Models. To fill this gap, we compare and contrast the climates of two idealized planets which build on the Simpler Models initiative of the Community Earth System Model (CESM). Using the fully coupled CESM, the Aqua configuration is ocean‐covered except for two polar land caps, and the Ridge configuration has an additional pole‐to‐pole grid‐cell‐wide continent. Contrary to most sea surface temperature profiles assumed for atmosphere‐only aquaplanet experiments with the thermal maximum on the equator, the coupled Aqua configuration is characterized by a global cold belt of wind‐driven equatorial upwelling, analogous to the eastern Pacific cold tongue. The presence of the meridional boundary on Ridge introduces zonal asymmetry in thermal and circulation features, similar to the contrast between western and eastern Pacific. This zonal asymmetry leads to a distinct climate state from Aqua, cooled by ∼2°C via the radiative feedback of clouds and water vapor. The meridional boundary of Ridge is also crucial for producing a more Earth‐like climate state compared to Aqua, including features of atmospheric and ocean circulation, the seasonal cycle of the Intertropical Convergence Zone, and the meridional heat transport. The mean climates of these two basic configurations provide a baseline for exploring other idealized ocean geometries, and their application for investigating various features and scale interactions in the coupled climate system. Plain Language Summary: Simplified climate models can improve our understanding of the Earth's climate system by stripping down its complexities. For example, atmospheric scientists often use idealized models with fixed sea surface temperature that is uniform in the east‐west direction. Meanwhile, oceanographers often use box‐shaped models driven by fixed wind. Although simplified models with full atmosphere‐ocean interactions are few, previous studies have shed light on fundamental processes governing Earth's climate, including the poleward transport of energy. However, the coarse "pixel size" and overly reduced components are hard to relate to contemporary models for international climate assessments. To bridge this gap, we present two simplified models within components and resolution similar to that of state‐of‐the‐art climate models. The nominally ocean‐covered model, without continents blocking the east‐west direction, develops a global cold belt of upwelling around the equator. In contrast, the model with an additional pole‐to‐pole strip continent is more Pacific‐like with a western pool and eastern cold tongue. While broadly consistent with previous works, these new models show more details in the tropical region that affect the Hadley cells and rainfall. The capability of these simplified models is promising for addressing atmosphere‐ocean interactions of scientific and societal interests, such as El Niño and hurricanes. Key Points: Two baseline examples of fully coupled CESM with idealized ocean geometry capture many features of Earth's circulation The nominally ocean‐covered coupled model has a global cold belt of equatorial upwelling and corresponding "reverse Hadley" cells The addition of a pole‐to‐pole strip continent leads to zonal asymmetry that makes the model's circulation more Pacific‐like